A Taguchi design approach for the enhancement of a detergent‐biocompatible alkaline thermostable protease production by Streptomyces mutabilis strain TN‐X30. Issue 4 (9th February 2022) - Mechri, Sondes; Bouacem, Khelifa; Chalbi, Taha‐Bilel; Khaled, Marwa; Allala, Fawzi; Bouanane‐Darenfed, Amel; Hacene, Hocine; Jaouadi, Bassem
Abstract: The ability of microorganisms to grow at high temperature, alkaline pH, and high salinity makes them an attractive target for enzyme‐production with several industrial applications. One strain TN‐X30 has been selected as protease producer and identified as Streptomyces mutabilis after a phenotypic and molecular study. Its production of protease was improved using Taguchi L27 design. The strategy was carried out to identify the optimum levels and the interaction of the screened factors. Following this step, maximum protease activity (10, 895 U/ml) was achieved after 6‐days of incubation. The TN‐X30 protease activity had an optimum of pH and temperature of 10 and 65°C, respectively. Thermodynamic parameters at 60°C were enthalpy 14.26 kJ/mol, entropy −220 J/mol/K, and Gibbs free energy 90.53 kJ/mol. TN‐X30 protease production displayed a 16‐fold increase reaching 175, 000 U/ml in a 100‐L fermentor. Furthermore, the lyophilization in presence of sorbitol enhanced the stability of the TN‐X30 protease which remained active at 75% after 24‐months of storage. The lyophilized TN‐X30 protease exhibited exceptional stability indexes in presence of some known commercialized detergent components as NEODOL® 25‐7, Dehydol® LT 7, Na2 CMC, Galaxy LAS, Galaxy LES 70, Galaxy 110, Galaxy CAPB Plus, and Sulfacid K. The lyophilized enzyme also displayed high stability with respect to both solid and liquid detergents. Finally, TN‐X30 protease exhibited remarkable destaining of blood, egg, and chocolate stained cloth pieces. These findings may promote TN‐X30 protease for use as bioadditive in detergent formulation, thereby reducing environmental chemical threat. Abstract :